Performance Analysis of Transcritical CO2 Refrigeration Cycle with Mechanical Subcooling Employing Zeotropic Mixture as Working Fluid - Dai Baomin; Liu Shengchun; Sun Zhili; Ma Muyu; Chen Qi; Ma Yitai (Zhileng xuebao)
A novel transcritical CO2 refrigeration cycle by utilizing zeotropic mixture as working fluid for the mechanical subcooling (MS) cycle is proposed in this study, which can be utilized to subcool the CO2 fluid flowing from the gas cooler. A maximum overall COP is achieved at the optimum discharge pressure and optimum subcooling degree. The results indicate that the maximum overall COP, optimum subcooling degree, and discharge pressure are closely related to the temperature glide. Additionally, the energy efficiency of CO2 refrigeration cycle is improved efficiently and the high pressure is reduced significantly when mixtures with proper temperature glide are used as the refrigerant of MS cycle. When compared with the base CO2 refrigeration cycle, the overall COP is enhanced by 46.53%, and discharge pressure is reduced by 2.758 MPa at an evaporation temperature of ﹣40 ℃ and ambient temperature of 35 ℃ when R32/R152a (40/60) is employed. The overall COP enhancement is significantly linked to the temperature glide. Furthermore, the thermal performance of the overall cycle is more significantly enhanced for hot or warm climate regions or relatively low evaporation temperature applications such as freezing and cold storage.